2020
DOI: 10.1002/agj2.20380
|View full text |Cite
|
Sign up to set email alerts
|

Liquid swine manure as a sidedressed nitrogen source for corn

Abstract: Sidedressing liquid swine (Sus scrofa) manure (LSM) on corn (Zea mays L.) may provide additional time to apply manure and help better match crop-nutrient demand with nutrient supply. A 2-yr, on-farm study was conducted in Minnesota to assess three sidedress nutrient sources-injected LSM via dragline hose, anhydrous ammonia (AA), and urea ammonia nitrate (UAN)-against a non-sidedressed control. At planting, all treatments (including the control) received 46 kg N ha −1 as starter fertilizer. At sidedressing, 157… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…The authors reported using a dragline system to sidedress corn with manure reduced soil compaction, application time, and costs compared to tanker application (Arnold et al, 2018). Pfarr et al (2020) sidedressed corn with a dragline manure system in Minnesota and found grain yield was similar to sidedressed commercial fertilizers (anhydrous ammonia and UAN) in 1 of 2 yr. They reported technical and weather-related issues with application in the 2nd year, indicating that the practice still needs to be fine-tuned (Pfarr et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The authors reported using a dragline system to sidedress corn with manure reduced soil compaction, application time, and costs compared to tanker application (Arnold et al, 2018). Pfarr et al (2020) sidedressed corn with a dragline manure system in Minnesota and found grain yield was similar to sidedressed commercial fertilizers (anhydrous ammonia and UAN) in 1 of 2 yr. They reported technical and weather-related issues with application in the 2nd year, indicating that the practice still needs to be fine-tuned (Pfarr et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…An * above a bar represents a significant difference from the control within hybrid and site-year at P < .05 farmers. Arnold (2015) and Pfarr et al (2020) reported that dragging a hose over corn while applying liquid swine manure increased grain moisture at harvest by 5 and 21 g kg −1 , respectively. These were lower than found in this study, although corn was dragged at V3 and V4, respectively, in those studies.…”
Section: Grain Moisturementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in Treatment 1, such decline may be due to the excess of nutrients present. According to [57] the increased rate of swine manure application increased the plant levels of nitrogen, potassium, and phosphorus along with the decline of recovery of plant nutrients, which may leech off potential pollutants to surface and ground waters [35], [58].…”
Section: Growth Performance Of Pechay (Brassica Rapa)mentioning
confidence: 99%